Applications of Potassium Fertilizer and Bacillus Sp. Biopesticide for Increasing Tomato Resistance to Bacterial Wilt Disease - Prihatiningsih, Nur; Djatmiko, Heru Adi; Rochminarsi, Eny (AGRIVITA, Journal of Agricultural Science, 2011)
Bacterial wilt on tomato caused by Ralstonia solanacearum is a crucial disease, because it can reduce yield until 50%. The aims of this research were: 1) to find out biopesticide formula for Bacillus sp.growth, 2) to test Bacillus sp. against R. solanacearum in vitro, 3) to test potassium fertilizer combined with Bacillus sp. for enhancing tomato resistance to the bacterial wilt disease. The research was conducted in 2 steps i.e to test the persistence of Bacillus sp. In biopesticide formula, and to test the best combination of both potassium and the Bacillus sp. biopesticide. The results showed that Bacillus B298 was the best isolate in its persistence on the biopesticide formula of organic growth medium+CaCO3+CMC 1%+mannitol 1%, and in inhibiting R. solanacearum. The best biopesticide formula for the Bacillus sp. persistence was growth organic media+ CaCO3+CMC 1%+mannitol 1%. Bacillus sp. was able to increase tomato resistance to the bacterial wilt disease from the category of susceptible to be tolerant and becoming resistant.   Keywords: tomato, Ralstonia solanacearum, potassium and Bacillus sp.